Zetcil: Game Mechanic Framework for Unity Game Engine - Rikman Roedavan; Agus Pratondo; Rio Korio Utoro; Apriyanti Putri Sujana (IJAIT (International Journal of Applied Information Technology), 2020)
Games are interactive multimedia products that require programming logic and graphic design capabilities in the development process. Game development using Unity Game Engine has become a primary subject in the Multimedia Engineering Technology study program, School of Applied Sciences, Telkom University. In the initial observation, it was found that more than 33% of students have difficulties in making a game using the C# language for Unity. The students understand the Game Design Pattern logic but having difficulty when applying it into programming codes. This research proposes Zetcil, a Game Mechanic Framework that simplifies the game development process for the Unity Game Engine. This framework turned most of the text-based programming commands into visual properties. Based on research for two years, it concluded that the Zetcil could increase 36% of student's confidence to develop games prototype rapidly.